Benign fibrous histiocytoma in a 7-year-old boy. - Ferrante, M. (European Journal of Pediatric Dermatology, 2011)
Case report. A 7-year-old boy was first observed due to the presence of a tumor on the forehead arisen from about 3 months and still growing according to his parents. Physical examination revealed a nodule of about 5.5 mm, brownish in color, with a small central depression, where the skin was ulcerated (Fig. 1). The nodule, movable on the deep layers, had hard-elastic consistency. It was removed under general anesthesia and the histologic examination (Fig. 2) showed slightly acanthotic epidermis, but ulcerated in the center. Immediately below the epidermis there was a tumor that occupied most of the dermis till to the subcutaneous tissue, consisting of elongated, fibroblastic in appearance cells, with storiform arrangement; in the upper dermis telangiectatic vessels were present (Fig.3). The pathological findings led to the final diagnosis of benign fibrous histiocytoma.